Partial Strength Beam-to-column Connection of Cold-formed Single Channel Section: Numerical and Experimental Study - Faisal, Amsyar; Cher, Siang Tan; Shahrin, Mohammad; Mahmood, Md Tahir; Hazlan, Abdul Hamid (Academy of Sciences Malaysia., 2021)
A full understanding of complex structural behaviour can be developed perfectly by using the combination of experimental and numerical approach. Although the basic method to determine the moment-rotation responses of the beam-to column CFS joints has recently established from the full scale testing, practising the finite element modelling (FEM) nowadays could explore in-depth on the number of variables and potential failure modes. In this paper, three dimensional (3-D) model to simulate the actual behaviour of the beam-to-column CFS joints has been proposed by using multi-purpose finite element package ABAQUS version 6.14 in order to validate analysis data against the experimental works. The approach of nonlinear material characteristics, contact and sliding between different components and adopting C3D8R solid elements are proposed in this model. A total of three (3) beam-to-column CFS connections consisting of three different types of beam depths were tested in isolation in order to observe the structural behaviour based on its strength and stiffness. Comparisons between experimental and FE analysis results in term of ultimate moment capacity have shown a good correlation with strength ratios ranging from 1.12 to 1.17. Therefore, it is possible to develop a realistic model for future parametric studies such as type and configurations of the connections.